Features of interaction between styrene-acrylic film formers and modified kaolin - Мережко, Ніна Василівна; Шульга, Ольга Сергіївна (Technology audit and production reserves, 2015)
The processes of interaction in systems of kaolin with modifiers and styrene-acrylic film former are analyzed in the article. Researches were performed using infrared spectroscopy. The aim of the work was to assess the level of interaction processes in the investigated systems. In this paper the quantitative parameters of the main characteristic bands responsible for the stretching vibrations of reactive groups of kaolin and film former are determined. Maximum shift of the characteristic bands of the IR spectra and change their intensity are indicated. It is determine which of the investigated surfactants provide the most complete interaction of kaolin with styrene-acrylic film former. The results demonstrates that the interactions of the modifiers, fillers, and film former are proceed in presence of OH-groups of adsorbed water and linkages Si-O-Al of kaolin surface. The authors suggest the use of modified kaolin, which are characterized by the most complete interaction with the styrene-acrylic film former, as fillers for waterborne paints that provide higher performance properties of coatings.